Kajian Hukum Terhadap Perlindungan Indikasi Geografis (Ig) Pada Tenun Ikat Bajawa Sebagai Warisan Tradisional - Ferdinandus Rema; Sudiyana (Jurnal Hukum Lex Generalis, 2026)
Geographical Indication (GI) protection is a legal instrument within the intellectual property regime aimed at safeguarding products whose distinctive characteristics are inseparable from geographical factors and local wisdom. Bajawa Ikat Weaving from Ngada Regency, East Nusa Tenggara, has strong potential for GI protection due to its historical, philosophical and communal values inherited across generations. However, despite its cultural significance and economic potential, Bajawa Ikat Weaving has not obtained official GI registration, indicating a gap between legal potential and implementation. This study aims to analyze the legal framework governing GI protection for Bajawa Ikat Weaving under Law Number 20 of 2016 concerning Trademarks and Geographical Indications, identify implementation challenges and formulate strengthening strategies. This research applies a normative-empirical legal approach using statutory, conceptual and sociological methods. Data were collected through literature review and online in-depth interviews with three purposively selected informants: a local artisan, a regional government or MSME representative and a cultural figure or community representative in Ngada Regency. The findings indicate that GI is an appropriate legal mechanism for protecting Bajawa Ikat Weaving as communal traditional wealth. However, implementations remains constrained by weakness institutional capacity, limited product documentation, low legal awareness among artisans and product imitation risks. Comparative analysis with Gayo Coffee and Muntok White Pepper demonstrates that strengthening institutional governance, digital documentation and stakeholder coordination are essential to accelerate GI registration and ensure sustainable legal protection.